2005
DOI: 10.1007/s10529-005-7870-4
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression and visualization of Mat-8 (FXYD-3) tagged with a fluorescent protein in Chinese Hamster Ovary (CHO)-K1 cells

Abstract: A type I transmembrane protein, Mat-8 (FXYD-3), was tagged with fluorescent protein, Discosoma red fluorescent protein, at the carboxyl terminal cytoplasmic tail, and stably expressed in Chinese Hamster Ovary (CHO)-K1 cells. The fluorescence signal was distributed in intracellular membranes, being not only detected around the nuclear envelope but also partly overlapping with an endoplasmic reticulum marker. Subcellular fractionation by density gradient centrifugation supported this partial overlapping. The sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…CHO-K1 cells were cultured in Ham's F-12 medium (GIBCO) supplemented with 7% (v/v) fetal bovine serum (JRH Biosciences) [13]. Transient transfection was carried out as follows: on a Lab-tek II 4-well chamber slide (NalgenNunc), 5 × 10 3 cells were seeded in 1 ml of the medium and then cultured overnight.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…CHO-K1 cells were cultured in Ham's F-12 medium (GIBCO) supplemented with 7% (v/v) fetal bovine serum (JRH Biosciences) [13]. Transient transfection was carried out as follows: on a Lab-tek II 4-well chamber slide (NalgenNunc), 5 × 10 3 cells were seeded in 1 ml of the medium and then cultured overnight.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Cells were cultured further for 24 hr and subjected to analysis by immunofluorescence microscopy. Stable transformants were isolated in the presence of 0.1 mg/ml G418 (Nacalai) [13].…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammary tumor 8 kDa (MAT8)/FXDY domain-containing ion transport regulator 3 (FXYD3), a FXYD-containing Na,K-ATPase ion channel regulator, was first identified as a protein highly expressed in murine breast tumor initiated by oncogenic ras (v-Ha-ras) or neu (her2, egfr2) [1][2][3][4][5][6][7][8][9][10][11][12][13] and later demonstrated to occur at (inner-) cellular membranes and to be involved in the regulation of chloride conductance. [11][12][13] Recent studies found FXYD3 to be overexpressed breast, prostate, and pancreatic cancers, 5,14,15 and suggested that it promotes carcinogenesis by providing a growth advantage.…”
mentioning
confidence: 99%
“…[11][12][13] Recent studies found FXYD3 to be overexpressed breast, prostate, and pancreatic cancers, 5,14,15 and suggested that it promotes carcinogenesis by providing a growth advantage. 14,15 Moreover, its expression was reported to be up-regulated in response to stimuli inducing cellular differentiation 16 and by treatment with an anticancer drug, 5-fluofouracil, in colon and/or breast cancer cells.…”
mentioning
confidence: 99%